Kraji spomina na soško fronto v 1. svetovni vojni - Matajc, Vanesa (Ars et humanitas, 2018)
The article examines the Slovene-Italian border space in terms of the historicalspatial identity that was ascribed to it by the collective imagination of World War I and the Isonzo front. Its meaning was created by the collective memories of the national communities that were involved in the battles on the Isonzo front. The paper addresses the question of the memorial culturalisation of this space in light of New Historicism and the theory of semiotics, i.e. as interaction of spatial-rhetorical signs and verballinguistic semiotisation of these signs which was produced by literature, diaries and reports on the Isonzo front. The paper presents referential sites of memory (Redipuglia, San Michele, Doberdob, Oslavia) in view of the following texts: Doberdob, a novel written by Slovene literary author Prežihov Voranc, Austrian soldier Hans Pölzer's memories, Slovene catholic priest Alojzij Novak's diary, Austrian reporter Alice Schalek's report from the battlefield, and (as an aspect of an external observer) Ernest Hemingway novel A Farewell to Arms. These texts represent collective identities which endow this border space with the identitiy of the Isonzo front and give it additional meaning: a) historical: in the course of history meaning was produced in terms of national collective identities which refer also to this space; and b) in the contemporary trans-national collective memory meaning is produced through the humanist lens of the catastrophic character of WW I. Both of these aspects of collective memories are created in an interaction with the space of the Isonzo front and its verbal-textual semiotisations, whereby sites of memory of WW I create one of the central rhetorics of this space.
Keywords: 1. svetovna vojna; collective memory; Great War; Hemingway, Ernest; Isonzo front; kolektivni spomin; literatura in zgodovina; literature and history; nacionalna identiteta; national identity; Novak, Alojzij; Pölzer, Hans; Prežihov Voranc; retorika prostora; rhetoric of space; Schalek, Alice; soška fronta